Esthetics and smile‐related characteristics assessed by laypersons. Issue 2 (29th December 2017) - Wang, Cui; Hu, Wen‐jie; Liang, Ling‐zhi; Zhang, Yan‐ling; Chung, Kwok‐Hung
Abstract: Purpose: This study aimed to identify the characteristics of full‐smile images assessed by laypersons using visual analog scale measurement. Materials and Methods: A total of 176 young Chinese subjects (88 males and 88 females; 20‐35 years of age) with healthy dentogingival tissue were recruited to have their dynamic smiles captured using digital technology. A full‐smile frame image of each subject was selected and evaluated by 22 laypersons (11 males and 11 females; 20‐35 years of age) using visual analog scale measurement. Unattractive and attractive groups were designated according to the 25th percentile and 75th percentile of average visual analog scale score for the subjects, respectively. Eight smile variables were used to measure the characteristics of the full‐smile images. Pearson's Chi‐square test and unpaired t tests were used to analyze the data with significance level α = 0.05. Results: The visual analog scale measurement scores of unattractive and attractive subgroups, respectively, were 37.89 ± 2.12 and 50.67 ± 2.75 (male subjects), and 37.14 ± 2.80 and 51.92 ± 1.99 (female subjects). VAS scores were significantly different between subgroups for both male and female subjects ( P < .001). No significant differences were observed between male and female subjects ( P > .05). Conclusions: Attractive full‐smiles in young Chinese subjects demonstrated higher frequencies of average or low anterior smile line, average or low posterior smile line, upward upper lip curvature, and "broad and short" smile with high smile index. Clinical Significance: The smile variables of anterior smile line, posterior smile line, upper lip curvature, and smile index are predominant factors of smile attractiveness, which should be given priority to consider and manage in the anterior esthetic treatment plan.